Determination of an optimal priming duration and concentration protocol for pepper seeds (Capsicum annuum L.) - Hassen ALOUI; Maher SOUGUIR; Chérif HANNACHI (Acta Agriculturae Slovenica)
Seed priming is a simple pre-germination method to improve seed performance and to attenuate the effects of stress exposure. The objective of this study was to determinate an optimal priming protocol for three pepper cultivars (Capsicum annuum L.): ‘Beldi’, ‘Baklouti’ and ‘Anaheim Chili’. Seeds were primed with three solutions of NaCl, KCl and CaCl2 (0, 10, 20 and 50 mM) for three different durations (12, 24 and 36h). Control seeds were soaked in distilled water for the same durations. After that, all seeds were kept to germinate in laboratory under normal light and controlled temperature. Results indicated that priming depends on concentration, duration and cultivar. The best combinations that we obtained were: KCl priming (10 mM, 36h) for ‘Beldi’ cultivar, CaCl2 priming (10 mM, 36h) for ‘Baklouti’ cultivar and finally NaCl priming (50 mM, 24h) for ‘Anaheim Chili’ cultivar. Generally, priming had an effect on total germination percentage, mean germination time, germination index and the coefficient of velocity compared to control seeds. The beneficial effect of seed priming could be used for improving salt tolerance on germination and early seedling growth for pepper cultivar.